Management of Cervical Cancer in Pregnant Women: A Multi-Center Retrospective Study in China - Li, Mingzhu; Zhao, Yun; Qie, Mingrong; Zhang, Youzhong; Li, Longyu; Lin, Bei; Guo, Ruixia; You, Zhixue; An, Ruifang; Liu, Jun; Zhang, Zhijun; Bi, Hui; et al. (Frontiers in Medicine, 2020)
Background: This retrospective multi-center study aimed to describe the epidemiological characteristics, clinical features, and management of patients with cervical cancer in pregnancy (CCIP) and evaluate maternal and infant outcomes. Methods: The data of patients with CCIP were retrospectively collected from those diagnosed and treated in 17 hospitals in 12 provinces in China between January 2009 and November 2017. The information retrieved included patients’ age, clinical features of the tumor, medical management (during pregnancy or postpartum), obstetrical indicators (i.e., gestational age at diagnosis, delivery mode, and birth weight), and maternal and neonatal outcomes. Survival analyses were performed using Kaplan–Meier survival curves and log-rank tests estimated patients' overall survival. Results: 105 women diagnosed with CCIP (median age = 35 years) were identified from approximately 45,600 cervical cancer patients (0.23%) and 525,000 pregnant women (0.020%). The median gestational age at cancer diagnosis was 20.0 weeks. The clinical-stage of 93.3% of the patients with CCIP was IB1, 81.9% visited the clinic because of vaginal bleeding during pregnancy, and 72.4% had not been screened for cervical cancer in more than five years. For analyses of cancer treatments received during pregnancy, patients were grouped into termination of pregnancy (TOP, n = 67) and continuation of pregnancy (COP, n = 38) groups. Analyses suggested that the TOP group was more likely to be diagnosed at an earlier gestational stage than the COP group (14.8 vs. 30.8 weeks, p < 0.001). The unadjusted hazard ratio for the COP group's overall survival was 1.063 times the TOP group’s (95% confidence interval = 0.24, 4.71). There were no significant differences between the TOP and COP groups in maternal survival (p = 0.964). Thirty-three of the infants of patients with CCIP were healthy at the end of the follow-up period, with a median age of 18 ± 2.8 months. Conclusions: Most patients with CCIP had not been screened for cervical cancer in over five years. The oncologic outcomes of the TOP and COP groups were similar. A platinum-based neoadjuvant chemotherapy regimen could be a favorable choice for the management of CCIP during the second and third trimesters of pregnancy.